La exportación de saber-hacer en materia de seguridad: la Policía Nacional de Colombia como experto en seguridad (2010-2022) - Eldi Paola Robayo (Nuevo mundo - Mundos Nuevos)
The export of security-related know-how has become a strategic component of Colombia’s foreign policy over the past two decades. This article aims to describe and analyze the role of the National Police of Colombia in this export between 2010 and 2022. Using a mixed methodological approach that combines qualitative analysis and the systematization of quantitative data, it examines the institutional guidelines underpinning this policy, the volume and characteristics of the training programs offered, and the deployment of experts abroad. Additionally, the cases of Mexico and Honduras are analyzed in depth as representative cooperation experiences. The article highlights the functioning of the triangular cooperation model, in which Colombia provides training while the United States contributes funding and logistical support. The analysis identifies the implications of this strategy, including its alignment with a militarized security approach, the limited evaluation of its actual impacts, and the risks of replicating problematic practices in institutionally fragile contexts.